PENERAPAN KONSEP FINITE STATE AUTOMATA PADA VENDING MACHINE DALAM PEMBELIAN KARTU E-MONEY SEMUA BANK KONVENSIONAL - Rini Novi Ambarwati; Anggun Yuli Asih; Sri Rahayu; Hafifah Bella Novitasari; Windu Gata (METHOMIKA: Jurnal Manajemen Informatika & Komputerisasi Akuntansi, 2021)
In the field of land transportation in the Capital City of DKI Jakarta, which is currently integrated with each other with payment methods in one tab, e-money cards can make it easier for users of public transportation modes whose mobility they often use and new users. With the enthusiasm of the community, until now there are still users of public transportation modes who just want to try using or who are switching to using public transportation modes to save more time and savings in terms of daily expenses. However, there are still those who do not have an e-money card, which requires users to buy an e-money card at a bank or supermarket that provides e-money cards. This study aims to make it easier for new users of public transportation to purchase e-money cards at each provider bank using a Vending Machine (VM) with the concept of the Finite State Automata (FSA) method of the Non-Deterministic Finite Automata (NFA) type. The results of this study aim to help new users of public transportation to be able to reach every station and bus stop in purchasing e-money cards, even though currently purchasing e-money cards with Vending Machines has not been spread evenly in several places of public transportation and is only focused on Vending. Machine one bank only.